Pentingnya Peran Arsip di Lingkungan Perguruan Tinggi - Wylda O Kowey; Alfonso V Poserattu; Eline O Hutubessy (Jurnal Administrasi Terapan, 2024)
The purpose of records management is to unify information, facilitate access and retrieval of information, secure archives/documents, increase utilization and utilization of archives. Higher education as an educational institution has academic administration documents. As an educational institution, it produces the most scientific work documents (vital, important, and useful documents) that must be secured. Therefore, higher education institutions need to form an archive management work unit, recruit management/archivists who have competence in the field of archives, immediately take inventory of archives with high use value, historical archives of institutions and archives of scientific work and research archives, it is hoped that there will be a policy higher education leaders to develop archiving activities because archives are records as a collective memory of the existence of an institution/institutionKeywords: Archieve management, Institution Archieve, Archieve Inventory.